A RECENT OVERVIEW OF LOCALLY ADMINISTERED TOPICAL OTIC DOSAGE FORMS - YAPAR, Evren ALGIN; BESKAN, Umut; KARAVANA, Sinem Yaprak (Universal Journal of Pharmaceutical Research, 2019)
Ear diseases can significantly affect the life quality of patient, so the need for effective treatment encourages the development of new active substances and new dosage forms. Otic dosage forms may be solutions, suspensions, or emulsions of drops or spray for washing the ear or for administration to the ear canal. They may be ear-wash preparations in the form of solution or emulsion, or medicated semi-solid or solid preparations in the form of gel, cream, ointment, powders, sticks or buffers. These preparations can contain one or much more active ingredients in a suitable vehicle and additionally may contain different excipients for isotonisation, pH adjustment, viscosity or solubility enhancement, buffering, preservation, etc. These excipients should not alter the pharmacological effect of active substances and should not be toxic or irritating. Ear preparations can be packaged in single or multiple doses. It is anticipated that otic dosage forms will be improved and the importance of locally applied, safe and highly controlled drug delivery systems will increase in the future. Peer Review History: Received 4 June 2019; Revised 11 July; Accepted 29 August; Available online 15 September 2019 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Dr. Iman Muhammad Higazy , National Research Center, Egypt, imane.higazy@hotmail.com Dr. George Zhu , Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com